Finite element analysis of maxillary incisor displacement during en-masse retraction according to orthodontic mini-implant position - Song, Jae-Won (Korean J Orthod, 2016)
OBJECTIVE: Orthodontic mini-implants (OMI) generate various horizontal and vertical force vectors and moments according to their insertion positions. This study aimed to help select ideal biomechanics during maxillary incisor retraction by varying the length in the anterior retraction hook (ARH) and OMI position. METHODS: Two extraction models were constructed to analyze the three-dimentional finite element: a first premolar extraction model (Model 1, M1) and a residual 1-mm space post-extraction model (Model 2, M2). The OMI position was set at a height of 8 mm from the arch wire between the second maxillary premolar and the first molar (low OMI traction) or at a 12-mm height in the mesial second maxillary premolar (high OMI traction). Retraction force vectors of 200 g from the ARH (-1, +1, +3, and +6 mm) at low or high OMI traction were resolved into X-, Y-, and Z-axis components. RESULTS: In M1 (low and high OMI traction) and M2 (low OMI traction), the maxillary incisor tip was extruded, but the apex was intruded, and the occlusal plane was rotated clockwise. Significant intrusion and counter-clockwise rotation in the occlusal plane were observed under high OMI traction and -1 mm ARH in M2. CONCLUSIONS: This study observed orthodontic tooth movement according to the OMI position and ARH height, and M2 under high OMI traction with short ARH showed retraction with maxillary incisor intrusion.